(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Although Kazakh kyui is quite laconical musical composition in duration aspect (it can last from one and half minute up to 5-6 minutes), there are no certain limits for it in the matter of topics and musical programming types that can be applied to. Even in such tiny span kyui is capable to alter its content several times: beginning mournfully it can easily end with the melody which is full of boundless energy (Kurmangazy – Kishkentai), or vice versa it can begin cheerfully and then proceed into the mood of thoughtful melancholy (Tattimbet – Bes Tore), and, furthermore, successively plucking the strings in «shertpe» tradition can be switched to fast melody (K. Akhmediyarov – Khaman Tolghau, Kutkende).Therefore the proposed article aims to examine the kyui compositions that are based on humorous situations provoked by a word and the relationship between the kyui and myths or folk legends as coherent parts of an artistic synthesis.